The Scenario Model of Aesthetic Plastic Surgery Business for Preparing a Thai Popular Culture Wave on Medical Tourism - Ritwatthanavanich, Natprapas; Thoongsuwan, Amorn; Pavapanunkul, Shayut (Asian Interdisciplinary and Sustainability Review, 2019)
Presentably, the rapid growth, medical tourism generated to improve insight into aesthetic plastic surgery business and cross-border care present opportunities for unprecedented economic growth. Advanced in the success in exporting a popular culture as export business or marketing mix for service marking such as Korean wave, Japanese wave etc. The revenue and the countries image include nation brand generated from medical and aesthetic plastic surgery travelers is very important economic incentive for the firm, the popular scenario model and governments to pursue these activities. Its impact on medical tourism and aesthetic plastic surgery services to establish the popular culture scenario model as practicing model benefits, Thailand also need. Relevantly, both medical tourism and aesthetic plastic surgery business need to design a Thai popular culture wave related the country image or nation branding by using influencing conceptual framework as follows 1) related to trends towards the factor conditions 2) ideal-typical scenario model imperative United Nations Environmental Programme (UNEap-GEO-3) and the influence of awareness and acceptance of brand resilience for managing risk and recovery in a high-speed of the rapid growth of medical tourism and aesthetic plastic surgery business. So far, regarding the success in a Thai popular culture of medical tourism and aesthetic plastic surgery business. Absolutely, the aims of this study is to identify, analyze and syntheses these influencing conceptual framework of their results can be designed the scenario model in order to establish a Thai popular culture wave it’s strongly acceptance relies on the Delphi expert consensus and using Index of Congruence (IOC) to test expert consensus from another group for content validity acceptance in this visionary scenario model. Respectively, it could be used to design and development to the practicing scenario model suggested that originality conceptual model to strengthening existing for seeding Thailand branding.